BB-Gen: A Packet Crafter for Data Plane Evaluation - Cesen, Fabricio; Patra, P. Gyanesh; Rothenberg, Christian (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2018: Anais Estendidos do XXXVI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2018.14174, 2018)
With the advent of research on fast path packet processing, trafﬁc generator tools witnessed many entrants with features ranging from supporting list of protocols, analyzing network trafﬁc to measuring throughput and latency of packets. While approaching towards feature completeness, the tools are becoming more complex every time making it difﬁcult to port, manage, and use. BBGen with a sole focus on simplicity complements other trafﬁc generators instead of trying to replace them. BB-Gen is a simple CLI-based packet crafter to generate packet ﬂows formatted as PCAP ﬁles. The tool supports different standard protocols and creates the necessary traces for network function conﬁguration and testing. It allows creating PCAPs for worst and best case scenarios with all unique ﬂows or following ﬂow distributions published elsewhere. In this demo, we feature BB-Gen as used by the MACSAD development team to test P4-based software switch pipelines.